Parkinson’s Is Time on Your Side? Evidence for Difficulties with Sensorimotor Synchronization - Bieńkiewicz, Marta M. N.; Craig, Cathy M. (Frontiers in Neurology, 2015)
There is lack of consistent evidence as to how well PD patients are able to accurately time their movements across space with an external acoustic signal. For years, research based on the finger-tapping paradigm, the most popular paradigm for exploring the brain’s ability to time movement, has provided strong evidence that patients are not able to accurately reproduce an isochronous interval (i.e. Harrington, Haaland, & Knight, 1998). This was undermined by Spencer and Ivry (2005) who suggested a specific deficit in temporal control linked to emergent, rhythmical movement not event-based actions, which primarily involve the cerebellum. In this study we investigated motor timing of seven idiopathic PD participants in event-based sensorimotor synchronisation task. Participants were asked to move their finger horizontally between two predefined target zones to synchronise with the occurrence of two sound events at two time intervals (1.5 and 2.5 seconds). The width of the targets and the distance between them were manipulated to investigate impact of accuracy demands and movement amplitude on timing performance. The results showed that participants with PD demonstrated specific difficulties when trying to accurately synchronise their movements to a beat. The extent to which their ability to synchronise movement was compromised was found to be related to the severity of PD, but independent of the spatial constraints of the task.